Nabi Muhammad SAW Sebagai Komunikator Komunikasi Islam - Husni, Muhammad; Abdullah, Abdullah; Sikumbang, Ahmad Tamrin (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2025)
This paper examines the Prophet Muhammad SAW as a communicator of Islamic communication. The Prophet Muhammad SAW as a communicator in Islamic communication focuses on how the Prophet Muhammad's communication skills were an important aspect in the spread of Islamic teachings. This excellence lies not only in his verbal abilities, but also in his holistic, integrative and wisdom-filled approach in conveying Divine messages. Effective communication methods the Prophet Muhammad SAW used various communication methods, both verbal, written and behavioral. He often used parables and stories to convey deep moral and religious messages.